Bersujud di keheningan malam : III jalan menumbuhkan gairah Qiyamul Lail / Muhammad Shalih Ali Abdillah Ishaq; penerjemah, Muh Muhaimin, Nur Afifah; penyunting, A. Choiran Marzuki - ISHAQ, MUHAMMAD SHALIH ALI ABDILLAH; Muh Muhaimin; Choiran Marzuki, A. (Mitra Pustaka, 2014)
668 hlm. ; 21 cm.